Should the New Zealand Parliament Allow the Intellectual Property Office of New Zealand to Continue to Grant Patents for Isolated Human Genes? - Upperton, Ruth (Victoria University of Wellington Law Review, 2013)
It is time for New Zealanders to decide whether we want to allow patents over isolated human genes. In making this decision, we should take heed of the pitfalls other jurisdictions have encountered in this area. In this article, I determine the approach New Zealand intellectual property law should take to the patenting of isolated human genes, with reference to the arguments and issues raised by the Myriad Genetics litigation in the United States of America. I conclude that a nuanced approach should be adopted. Isolated human genes are not patentable subject-matter from a legal perspective; however, patents in the field of gene therapeutics should be allowed on policy grounds.